2022
DOI: 10.4149/neo_2021_210823n1206
|View full text |Cite
|
Sign up to set email alerts
|

Blocking stanniocalcin 2 reduces sunitinib resistance in clear cell renal cell carcinoma

Abstract: Stanniocalcin 2 (STC2) has been identified as a prognostic marker in renal cell carcinoma.However, the role of STC2 in renal cell carcinoma is still unclear. In this study, we investigated the relationship between high expression of STC2 and sunitinib resistance in cells and the underlying mechanism. Through GEPIA platform analysis based on the TCGA database, it showed that the expression of STC2 in kidney renal clear cell carcinoma (KIRC) was significantly higher than that in the normal population. Real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In our previous study, the sunitinib resistance of ccRCC cells in normoxia condition had been detected 30 . In the present study, we aimed to identify the efficacy of sunitinib on Caki-1 cells and the underlying mechanism under hypoxia conditions.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In our previous study, the sunitinib resistance of ccRCC cells in normoxia condition had been detected 30 . In the present study, we aimed to identify the efficacy of sunitinib on Caki-1 cells and the underlying mechanism under hypoxia conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Both in vivo and in vitro results indicated that STC1 mediated gemcitabine resistance in pancreatic ductal adenocarcinoma 39 . Our previous study showed that sunitinib treatments reduced the expression of STC2 both mRNA and protein levels, which could reduce sunitinib resistance of Caki-1 cells 30 . All these studies detected the roles of STCs in drug resistance under normoxia but not hypoxia, and the latter one is a real pathophysiological environment of tumors and important for the cancer incidence and development.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, several studies showed that STC2 is a protective factor for some tumors. STC2 reduces resistance to sunitinib in clear-cell renal cell carcinoma (Qin et al, 2022). STC2 inhibits migration and invasion of breast cancer via inhibition of PKC signaling (Hou et al, 1932).…”
Section: Introductionmentioning
confidence: 99%